So help me Todd. Season 1 [videorecording (DVD)] - Prendergast, Scott; Rubin, Amy York; Klaviter, Elizabeth; Cadrot, Thomas; Harden, Marcia Gay; Astin, Skylar, 1987-; Wise, Madeline (So help me Todd (Television program : 2023), 2023)
As a kid, Todd wanted nothing more than to be a private detective. Now that he is, he's quite good at it. The rest of his directionless life? That's a bit of a mystery, especially to his uber-successful lawyer mom. So when she offers him a job as an in-house investigator at her firm as a way for him to get his act together, he reluctantly agrees, as long as Mom promises to let her adult son be who he wants to be.